Urinary Tract Infection in Health Care Workers in Personal Protective Equipment during Covid – 19 Care an Online Survey - Srinivasan, Revathi; S, Josephine; Kumar, A.K. Vijay Krishna (International Journal of Medical Science and Clinical Research Studies, 2022)
Background: COVID -19 the corona virus disease 2019 pandemic in India made lot of changes in each individuals especially challenges to the health care workers and system in country. The personal protective equipment undoubtedly provides a shield of protection for the health care workers fighting against the disease. However there have been various problems associated with the personal protective equipment. There is need to understand the possible influence of personal protective equipment’s in health care workers leading to urinary tract infection during covid care. Aim: To find the effect of personal protective equipment leading to urinary tract infection in health care workers during covid care. Study design: Observational study.(0nline survey) Method: Sample size of 160 was taken between age group of 18 – 45 years in health care workers on the basis of inclusion and exclusion criteria. Samples collected through Google form Results: Statistical analysis of the data was done by using the software SPSS23.0 .Descriptive statistics were calculated and summarized. Which includes frequency, percentage, Mean and standard deviation. Personal protective equipment its not leading to urinary tract infection in health care workers during covid care. Conclusion: The conclusion of the survey was based on the responses, received from the HCWs through the goggle form, personal protective equipment its not leading to urinary tract infection in health care workers during covid care they able to handle or manage while wearing PPE kit during the covid duty. Based on the result of this study around 50.4% participants have the urinary urgency to remove the PPE kit. The study showed that HCWs challenged themselves with the personal protection as well as the public health. Therefore, this study could not predict the risk of urinary tract infection in health care workers while wearing PPE kit during covid care.